2018
DOI: 10.1111/eea.12709
|View full text |Cite
|
Sign up to set email alerts
|

Sexual competitiveness of fertile and sterile, wild and mass‐reared males of Anastrepha obliqua

Abstract: Anastrepha obliqua (Macquart) (Diptera: Tephritidae), commonly known as the West Indies fruit fly, is a pest species of mango, plum (both Anacardiaceae), and other commercial crops in various countries in the Neotropics, including Mexico, Central and South America, and the Caribbean islands. Currently, the sterile insect technique (SIT) is used to control this pest. Here, the sexual competitiveness of mass-reared sterile A. obliqua males was evaluated against wild males in field cages. In the first experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…In this study, the quality of the flies produced with the two methods was assessed. In tephritid fruit flies as well as in other insect species, mass-rearing conditions often compromise the quality of adults, e.g., damaged wings or shortened lifespan, reducing the performance of males after release in the field [52]. Our results showed that flies produced using the wax panel system were of better quality with regards to adult emergence and flight ability compared with the netted system.…”
Section: Discussionmentioning
confidence: 68%
“…In this study, the quality of the flies produced with the two methods was assessed. In tephritid fruit flies as well as in other insect species, mass-rearing conditions often compromise the quality of adults, e.g., damaged wings or shortened lifespan, reducing the performance of males after release in the field [52]. Our results showed that flies produced using the wax panel system were of better quality with regards to adult emergence and flight ability compared with the netted system.…”
Section: Discussionmentioning
confidence: 68%
“…Due to its economic impact and its ability to be polyphagous, A . obliqua has been widely studied, and information about its distribution on the American continent (Santos et al, 2019), intraspecific genetic variation and population structure (Martins de Almeida et al, 2019; Passos et al, 2018; Ruiz‐Arce et al, 2019; Velasco‐Cuervo et al, 2019), ecological interactions (Campanini et al, 2017; Mesquita et al, 2018; da Vargas et al, 2019), reproductive behaviours associated with the host plant (Hernández et al, 2019), formation of interspecific hybrids (Díaz et al, 2018; Rull et al, 2018) and composition of associated microbiota (Gallo‐Franco & Toro‐Perea, 2020; Ventura et al, 2018) has been obtained; in addition, mechanisms to control this pest, such as using chemical attractants, the sterile insect technique (Gallardo‐Ortiz et al, 2018b, 2018a) or biological control (Cancino et al, 2019; Murillo et al, 2019), have also been studied. All these works were conducted to understand the biology of this species and address the problem it represents for commercial crops.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, la presencia de esta especie en huertas de mango son motivo de estricta cuarentena por parte de Estados Unidos de América (Aphis, 1994). Debido a su impacto económico y su capacidad de ser polífaga, A. obliqua ha sido ampliamente estudiada, y hay datos sobre su distribución en el continente americano (Santos et al, 2019), variación genética intraespecífica y estructura poblacional (Martins de Almeida et al, 2019;Passos et al, 2018;Ruiz-Arce et al, 2019;Velasco-Cuervo et al, 2019), interacciones ecológicas (Campanini et al, 2017;Mesquita et al, 2018;da Vargas et al, 2019), comportamientos reproductivos asociados a la planta hospedera (Hernández et al, 2019); mecanismos para el control de esta plaga, como el uso de atrayentes químicos, la técnica del insecto estéril (Gallardo-Ortiz et al, 2018b, 2018a o el control biológico (Cancino et al 2019;Murillo et al, 2019). La comprensión sobre la ecología y el comportamiento de esta especie en Panamá está supeditada en muchas ocasiones a informaciones externas, por ello, es importante reportar sucesos de biología básica para un mayor entendimiento de nuestro entorno y de esa forma buscar alternativas ecológicas para el control de especies como esta.…”
Section: Introductionunclassified